Chemical Composition, Antiprotozoal and Cytotoxic Activities of Indole Alkaloids and Benzofuran Neolignan of Aristolochia cordigera - Pereira, Marcos D. P. [UNESP]; Silva, Tito da; Aguiar, Anna Caroline C.; Oliva, Glaucius; Guido, Rafael V. C.; Yokoyama-Yasunaka, Jenicer K. U.; Uliana, Silvia R. B.; Lopes, Lucia M. X. [UNESP] (Georg Thieme Verlag Kg, 2017)
This is a comparative study on the intraspecific chemical variability of Aristolochia cordigera species, collected in two different regions of Brazil, Biome Cerrado (semiarid) and Biome Amaznia (coastal). The use of GC-MS and statistical methods led to the identification of 56 compounds. A higher percentage of palmitone and germacrene-D in the hexanes extracts of the leaves of plants from these respective biomes was observed. Phytochemical studies on the extracts led to the isolation and identification of 19 known compounds, including lignans, neolignans, aristolochic acids, indole-beta-carboline, and indole alkaloids. In addition, two new indole alkaloids, 3,4-dihydro-hyrtiosulawesine and 6-O-(beta-glucopyranosyl)hyrtiosulawesine, were isolated and a new neolignan, cis-eupomatenoid-7, was obtained in a mixture with its known isomer eupomatenoid-7. Their structures were determined by spectroscopic methods, mainly by 1D- and 2D-NMR. The occurrence of indole alkaloids is being described for the first time in the Aristolochiaceae family. Moreover, the in vitro susceptibility of intracellular amastigote and promastigote forms of Leishmania amazonensis to the alkaloids and eupomatenoid-7 were evaluated. This neolignan exhibited low activity against promastigotes (IC50 = 46 mu M), while the alkaloids did not show inhibitory activity. The new alkaloid 6-O-(beta-glucopyranosyl) hyrtiosulawesine exhibited activity in the low micromolar range against Plasmodium falciparum, with an IC50 value of 5 mu M and a selectivity index higher than 50.
Keywords: Aristolochia cordigera; Aristolochiaceae; neolignans; indole alkaloids; antiplasmodial; antileishmanial